2022
DOI: 10.1063/5.0078556
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous runaway of fast turbulent flames for turbulence-induced deflagration-to-detonation transition

Abstract: One of the fundamental mechanisms for detonation initiation is deflagration-to-detonation transition (DDT). This research experimentally explores the runaway condition for highly turbulent fast flames before DDT, which are characterized by extremely high turbulent flame speeds. Such fast turbulent flames experience increased effects of compressibility and may develop a runaway acceleration combined with a pressure buildup that leads to a turbulence-induced DDT (tDDT) mechanism that has been recently reported. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…Our study showed that the spontaneous wave can evolve from an initial subsonic to the CJ velocity, most likely in the restricted area of the funnel of unreacted material, previously shaped by the flow, seen in some DDT scenarios near the tip of a turbulent flame zone whether in experiments 1 or in computations 51,52 . The analysis of Chambers et al 30 showed that a compressed region was formed ahead of non-planar flames, on the verge to collide, after which the runaway flame occured. A careful analysis of the temporally and spatially resolved experimental results of Meyer, Urtiew, and Oppenheim 1 showed that oblique shocks were also present within the tongue of fresh gases, see frames 3 to 7, as well as the occurrence of two explosion events.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our study showed that the spontaneous wave can evolve from an initial subsonic to the CJ velocity, most likely in the restricted area of the funnel of unreacted material, previously shaped by the flow, seen in some DDT scenarios near the tip of a turbulent flame zone whether in experiments 1 or in computations 51,52 . The analysis of Chambers et al 30 showed that a compressed region was formed ahead of non-planar flames, on the verge to collide, after which the runaway flame occured. A careful analysis of the temporally and spatially resolved experimental results of Meyer, Urtiew, and Oppenheim 1 showed that oblique shocks were also present within the tongue of fresh gases, see frames 3 to 7, as well as the occurrence of two explosion events.…”
Section: Discussionmentioning
confidence: 99%
“…This mechanism was independent of the turbulent structure of the flame, the combustion regime and the reactive mixture. Very recently, Chambers et al 30 experimentally explored turbulence-induced DDT. Poludnenko also showed that in other cases, the strong shock ran ahead of the flame brush.…”
Section: Introductionmentioning
confidence: 99%
“…Deflagration-to-detonation transition (DDT) is a fundamental physical phenomenon in astrophysics, cosmology, detonation engines, and the explosion of vapor clouds. [1][2][3] Detonation propagation has received extensive attention in recent years because controlled detonation propagation can potentially revolutionize the propulsion system, e.g., in a rotating detonation engine considers detonation propagation in a mixture with nonlinear and 2D periodic disturbance. Few studies have focused on this scenario.…”
Section: Introductionmentioning
confidence: 99%